Emigration Prospects and Educational Choices: Evidence from the Lorraine-Luxembourg Corridor - Michel Beine; Vincent Fromentin; Javier Sánchez Bachiller (CESifo GmbH, 2024)
An extensive literature has documented the incentive effect of emigration prospects in terms of human capital accumulation in origin countries. Much less attention has been paid to the impact on specific educational choices. We provide some evidence from the behavior of students at the University of Lorraine that is located in the northeast of France and close to Luxembourg, a booming economy with attractive work conditions. We find that students who paid attention to the foreign labor market at the time of enrollment tend to choose topics that lead to occupations that are highly valued in Luxembourg. These results hold when accounting for heterogeneous substitution patterns across study fields through the estimation of advanced discrete choice models. Incentive effects of emigration prospects are also found when accounting for the potential endogeneity of the interest for the foreign labor market using a control function approach based on the initial locations of these students at the time of enrollment. Consistently, students showing no attention to the foreign labor market are not subject to the incentive effect of emigration prospects.
Keywords: C25; F22; J61; 330; brain gain; emigration prospects; educational choices; discrete choice modelling; labor markets